Dependence of 1H-NMR T1 relaxation time of trimethylglycine betaine deep eutectic solvents on the molar composition and on the presence of water. Issue 5 (19th January 2023) - Allegretti, Chiara; D'Arrigo, Paola; Gatti, Francesco G.; Rossato, Letizia A. M.; Ruffini, Eleonora
Abstract : Our method for the assessment of the stoichiometric coefficients of trimethylglycine betaine/diol based DESs, by automated measures of 1 H-NMR T 1, compares well with other analytical techniques. Abstract : 1 H-NMR spin lattice relaxation times ( T 1 ), measured by inversion recovery technique, allowed to establish the stoichiometric coefficient (ratio between the H-bond acceptor and H-bond donor) of a series of trimethylglycine betaine/diol based deep eutectic solvents (DESs); ethylene glycol, triethylene glycol and 1, 3-propandiol were selected as H-bond donors. The maximum amount of water tolerated by the DES, before its complete hydration, was determined as well. Finally, the method was validated comparing the eutectic composition of the betaine/glycol system with that determined by means of differential scanning calorimetry analysis; the stoichiometric coefficients were identical.